FEMININE DIMENSION IN ISLAM AND THE ERA OF MASCULINIZATION TOWARD NATURE - Basri, Mohammad Hasan (EGALITA, 2011)
The development process which is running in several countries tends to ignore the aspect of natural balance. It leads to undesirable impact toward natural -ecosystem sustainability process and human beingsâ€™ life. In Vandana Shiva language, this recent development process is â€œmasculinizationâ€ process toward nature. Nature which is symbolized as mother earth is exploited destructively causing natural destruction and ecological crisis. In this paper, writer tries to find the root of problemform eco-feminism perspective through several theories on human and nature relationship related to feminism concept in Islam. There are two main reasons for recent exploitative and destructive development towards nature. First, human beings act as single authoritarian and single entity. Second, in Islamic theological perspective, recent development model is masculine -based and it ignores feminine aspects in Islam that it applies rigid and dominating approaches.Proses pembangunan yang berlangsung di berbagai negara saat ini cenderung mengabaikan aspek keseimbangan alam. Hal tersebut berdampak tidak saja berakibat buruk terhadap proses keberlangsungan ekosistem alam, akan tetapi juga mengancam terhadap keberlangsungan hidup manusia. Dalam bahasa Vandana Shiva, proses pembangunan saat ini ada proses â€œmaskulinisasiâ€ terhadap alam. Alam yang disimbolkansebagai â€œmother earthâ€ kemudian dieksploitasi secara dekstruktif sehingga menimbulkan kerusakan alam dan krisis ekologi. Dalam tulisan ini, penulis mencoba mencari akar persoalan tersebut dari perspektif ecofeminism melalui beberapa teori tentang hubungan manusi dan alam dikaitkan dengan dimensi feminitas dalam Islam. Ada dua hal penting yang mendasari mengapa saat ini pembangunan cenderung ekploitatif dan destruktif terhadap alam. Pertama, manusia merasa sebagai penguasa alam dan melihat dirinya sebagai entitas tunggal. Kedua, dalam perspektif teologis Islam, model pembangunan selama ini masih bersifat â€œmaskulinâ€ dan tidak memperdulikan aspek-aspek feminin dalam Islam, sehinggapendekatan yang digunakan masih bersifat rigid dan mendominasi.